Synthesis and Surface Behaviour of NDI Chromophores Mounted on a Tripodal Scaffold: Towards Self‐Decoupled Chromophores for Single‐Molecule Electroluminescence. Issue 47 (22nd July 2021) - Balzer, Nico; Lukášek, Jan; Valášek, Michal; Rai, Vibhuti; Sun, Qing; Gerhard, Lukas; Wulfhekel, Wulf; Mayor, Marcel
Abstract: This paper reports the efficient synthesis, absorption and emission spectra, and the electrochemical properties of a series of 2, 6‐disubstituted naphthalene‐1, 4, 5, 8‐tetracarboxdiimide (NDI) tripodal molecules with thioacetate anchors for their surface investigations. Our studies showed that, in particular, the pyrrolidinyl group with its strong electron‐donating properties enhanced the fluorescence of such core‐substituted NDI chromophores and caused a significant bathochromic shift in the absorption spectrum with a correspondingly narrowed bandgap of 1.94 eV. Cyclic voltammetry showed the redox properties of NDIs to be influenced by core substituents. The strong electron‐donating character of pyrrolidine substituents results in rather high HOMO and LUMO levels of ‐5.31 and ‐3.37 eV when compared with the parental unsubstituted NDI. UHV‐STM measurements of a sub‐monolayer of the rigid tripodal NDI chromophores spray deposited on Au(111) show that these molecules mainly tend to adsorb flat in a pairwise fashion on the surface and form unordered films. However, the STML experiments also revealed a few molecular clusters, which might consist of upright oriented molecules protruding from the molecular island and show electroluminescence photon spectra with high electroluminescence yields of up to 6×10 −3 . These results demonstrate the promising potential of the NDI tripodal chromophores for the fabrication of molecular devices profiting from optical features of the molecular layer. Abstract : Three‐legged race : The efficient synthesis, optical and electrochemical properties of a series of 2, 6‐disubstituted naphthalene‐1, 4, 5, 8‐tetracarboxdiimides (NDIs) mounted on a tripodal platform are reported. Moreover, their surface behaviour after spraying on Au(111) was studied. In a STML setup, such NDI tripods show electroluminescence photon spectra with high electroluminescence yields and thus demonstrate their potential for optoelectronic devices.